Power in organizations - "Pfeffer, Jeffrey." (Cambridge, 1981)
In the last few years there has been increased interest in a political perspective on organizational behavior. This interest has culminated in several books appearing at about the same time which treat aspects of power and politics in organizations. this growing concern with power and political activity encompasses analyses which use both social psychological as well as sociological perspectives, and incorporates topics as diverse as bargaining and influence strategies and the political aspects of organization development.
Keywords: Power (Social sciences)